Influência do ágar e do pH sobre o cultivo in vitro de embriões de laranja 'natal' - RIBEIRO, VALTEMIR GONÇALVES; RAMOS, JOSÉ DARLAN; CARVALHO, GLADYSTON RODRIGUES; JUNIOR, ARNALDO FREITAS DE OLIVEIRA (Revista Ceres, 2015)
.